To evaluate the effectiveness of the Japanese Encephalitis immunization programme. - De Alwis, K.L.N.S.K (My University, 2006)
The study revealed that a total of 123 patients with suspected viral encephalitis, viral meningitis and meningo encephalitis were admitted during the study period. Of these 35 patients h d died during the acute illness, giving an average case fatality rate of 28.4 percent peak admissions were in December 2002 and January 20J3. Both children and adults were affected and male to female ratio was 2: 1.The case fatality rate was not significantly different between males and females, whereas the case fatality rate of patients over 50 years was significantly different compared to other age categories (x2 = df-1 p<0.05). Japanese encephalitis (JE) was confirmed in 19.5 percent patients on the basic of the laboratory findings ( identification of JE specific IgM antibodies in cerebro spinal fluid (CSF) sample). 78.8 percent of patients were diagnosed as encephalitis, 14.1 percent were diagnosed as meningitis and the remaining 7.1 percent were diagnosed as meningo encephalitis of the 123 patients, BHTs of 85 patients (72.9 percent) had change in level of consciousness during the acute illness. Neck stiffness was percent in 44 paients ( 51.8 pecent) , convulsions in 25 patients (29.4 percent), abnormal behavior in 22 patients ( 25.9 percent), neurological signs in 19 patients (22.4 percent) and abnormal movements in 2 patients (2.3 percent). The age appropriate immunization coverage was 75.4 percent ( 95 percent C173.0-77.8) for the 3rd dose and 55.6 percent (9 percent 5 C1 73.0-77.8) for the 3rd dose and 55.6 percent ( 9 percent 5 C1 51.4-57.8) for the fouth dose dose o percent JE vaccine